New Understanding in Physics and Astronomy - Joseph J. Smulsky (New Understanding in Physics and Astronomy, 2023)
The shortcomings of the modern scientific picture of the world are associated with the currently accepted scientific method, in which almost all explanations of physical phenomena are based on hypotheses. The arbitrariness of accepted hypotheses is gradually forgotten, and invented explanations are affirmed as real structures of the world. In this paper, electromagnetic and gravitational interactions are considered from the standpoint of a non-hypothetical approach. Its essence lies in the study of phenomena as such, in the measurement of various properties of natural objects and in the establishment of relationships between them. The results obtained form a new understanding of the phenomena of the surrounding world. The laws of change in the frequency of light and its direction by a moving source follow from the laws of electromagnetism. The dynamics of the orbits of the planets over the interval of 100 million years was studied by a new numerical method and the stability of the Solar system was established. This method was used to study the evolution of the motion of two asteroids Apophis and 1950DA over a 1000-year interval. Various ways of converting their trajectories into the orbits of the Earth’s satellites are considered. It is proved that the observed rotation rate of Mercury’s perihelion coincides with that calculated from the Newtonian interaction of the planets and the compound model of the Sun’s rotation. As a result of the numerical solution of the equations, the influence of the planets, the Sun and the Moon separately on the rotational motion of the Earth for 10 thousand years was studied. The evolution of the Earth’s axis over 20 million years under the combined action of these bodies has been studied. It has been established that the Earth’s axis precesses relative to a fixed direction in space, different from the direction of precession of planetary orbits. It has been established those particles: neutrino, bosons etc. were introduced as a result of an incorrect theory of interactions in the Theory of Relativity. It is shown that gravitational waves do not exist. They were introduced to explain the excessive rotation of Mercury’s perihelion. However, it is due to the oblateness of the Sun.